2019
DOI: 10.1111/1440-1681.13073
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB as the mediator of metformin's effect on ageing and ageing‐related diseases

Abstract: Summary Ageing can be defined as the progressive failure of repair and maintenance systems with a consequent accumulation of cellular damage in nucleic acids, proteins, and lipids. These various types of damage promote ageing by driving cellular senescence and apoptosis. The nuclear factor‐kappa B (NF‐kB) pathway is one of the key mediators of ageing and this pathway is activated by genotoxic, oxidative and inflammatory stress, and regulates expression of cytokines, growth factors, and genes that regulate apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 104 publications
(203 reference statements)
5
49
0
1
Order By: Relevance
“…Using bioinformatic analysis of oncogene‐expressing senescence cells, Moiseeva et al reported that NF‐κB pathway is the most relevant transcription factor altered during senescence and inhibited by metformin treatment (Moiseeva et al, 2013). In agreement, Sultuybek et al revealed NF‐κB signaling as the target of the anti‐aging effect of metformin in dermal fibroblasts (Kanigur Sultuybek et al, 2019). In line with these observations, our data indicate that CKD MSCs had higher NF‐κB activity, and this effect was rescued by metformin treatment, resulting in a decrease in SASP.…”
Section: Discussionmentioning
confidence: 56%
“…Using bioinformatic analysis of oncogene‐expressing senescence cells, Moiseeva et al reported that NF‐κB pathway is the most relevant transcription factor altered during senescence and inhibited by metformin treatment (Moiseeva et al, 2013). In agreement, Sultuybek et al revealed NF‐κB signaling as the target of the anti‐aging effect of metformin in dermal fibroblasts (Kanigur Sultuybek et al, 2019). In line with these observations, our data indicate that CKD MSCs had higher NF‐κB activity, and this effect was rescued by metformin treatment, resulting in a decrease in SASP.…”
Section: Discussionmentioning
confidence: 56%
“…Our findings can also have potential therapeutic implications. For example, metformin is a drug that is commonly used for the treatment of type 2 diabetes and can have anti-senescence effects by modulating key intracellular pathways related to SASP (e.g., NFκB and p53) and reducing circulating SASP 5355 . Metformin can also lead to weight loss in overweight and obese diabetic and non-diabetic patients 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Its activation is associated with diverse upstream signaling pathways related to immune attacks, growth factors, and internal and external danger signals [78,79]. It regulates expression of hundreds of genes [80] that are mainly implicated in inflammatory responses and immune signaling, as those encoding cytokines and chemokines (tumor necrosis factor alfa-TNF-α and interleukins), growth factors and their receptors, pro-inflammatory enzymes (inducible nitric oxide synthase-iNOS and cyclooxygenase-2-COX-2 above all), other transcription factors, but also genes that regulate apoptosis and cell-cycle progression [81,82]. The increase of NF-κB pathway activity is associated with a whole-body persistent, low-level inflammation that characterizes the aging process [83,84].…”
Section: Modulatory Function Of Evoo Polyphenols On Nf-κb Expression mentioning
confidence: 99%